Post-traumatic stress disorder following childbirth: a neglected cause - Ahsan, Areeba; Nadeem, Abdullah; Habib, Ashna; Basaria, Areeba Aamir Ali; Tariq, Rabeea; Raufi, Nahid (Frontiers in Global Women's Health, 2023)
Post-traumatic stress disorder (PTSD) following childbirth is a significant mental health risk for women globally. However, it remains a neglected cause, particularly in low-income countries like Pakistan. This paper explores the unique challenges faced by women in such settings, including limited access to healthcare and social support, cultural norms, and stigma surrounding mental health. The diagnosis and causes of postpartum PTSD are discussed, along with its effects on both mothers and their infants. The lack of awareness and training among healthcare professionals in recognizing and treating postpartum PTSD is highlighted as a major barrier to adequate care. To address these challenges, the paper proposes a comprehensive approach, including raising public awareness, providing mental health support and resources, and integrating postpartum mental health into medical education. Trauma-focused therapies are recommended for effective treatment. The paper concludes with the need for more research in low-income countries and emphasizes the importance of understanding and supporting women with postpartum PTSD to improve their well-being and maternal and child health.